Teacher Is the Creator of the Pedagogical Environment in the Institution of Preschool Groups in Secondary School - Buboviča, Jana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Everyone from first to the last days of life are included in one or several groups: family, preschool education, preschool group or school, work environment, in social institutions. Currently, Latvian school children going to nursery schools and pre-school groups to educational institutions (schools, learning institutions, etc.) which are registered in the register of educational institutions and licensed early childhood education programs. Researching and analyzing the importance of pre-school education, it is important to recognize that early childhood education exercise a certain type of education and the extent to which, in accordance with the concepts and principles of the guidelines are designed curriculum, targeted programs for the acquisition of educational guidance and evaluation system. Educational institution as a complex system, changes in one component affects the other components in the quality and up to date further changes; System prosperity depends on the components of mutual unity: from the planning process, eligibility and conditionality for the development of a clear and purposeful strategy for raising educational institutions. Educational process - it is all a child's life, organized and managed by an adult. This should ensure the child's teaching and learning, development, education, education as a whole, and where much attention is paid to children's brain development, linking it with the child's active participation. It also set a goal: to study the role of pre-school teacher teaching environment for pre-school institution group of high school.